What do patients value about spinal manipulation and home exercise for back-related leg pain? A qualitative study within a controlled clinical trial. (December 2016) - Maiers, Michele; Hondras, Maria A.; Salsbury, Stacie A.; Bronfort, Gert; Evans, Roni
Abstract: Background: Patient perceptions may influence the effectiveness and utilization of healthcare interventions, particularly for complex health conditions such as sciatica or back-related leg pain (BRLP). Objectives: To explore BRLP patients' perceptions of spinal manipulative therapy (SMT) and home exercise with advice (HEA). Design: Qualitative study in a controlled clinical trial. Method: Semi-structured interviews conducted after 12 weeks of treatment asked participants about satisfaction with care and whether treatment was worthwhile. An interdisciplinary research team conducted content analysis using qualitative data analysis software to identify and summarize themes. Results: Of 192 trial participants, 174 (91%) completed interviews (66% female, age 57.0 ± 11.5 years). Participants identified interactions with providers and staff, perceived treatment effects, and information as key contributors to both their satisfaction and the worthwhile nature of treatment. HEA was liked for its convenience and ability to foster an exercise habit. SMT was liked for specific aspects of the modality (e.g. manipulation, stretching) and provider competency. Most participants reported no dislikes for SMT or HEA, but some noted the dose/time commitment for SMT and discipline of HEA as least liked aspects of the interventions. Conclusions: The quality of patient–provider interactions, perceived treatment effects, and information sharing influenced BRLP patients' satisfaction with care. Qualitative research describing patients' preferences can facilitate translation of study findings into practice and allow clinicians to tailor treatments to facilitate compliance and satisfaction with care. Graphical abstract: Highlights: Understanding patient perceptions may improve outcomes for challenging conditions like sciatica. Satisfaction is influenced more by interaction with providers than changes in symptoms. Perceived treatment effects, including back related leg pain and function, make care "worthwhile". Global outcome measures may not capture the range of factors that influence satisfaction.